2019
DOI: 10.5334/labphon.131
|View full text |Cite
|
Sign up to set email alerts
|

Variation in children’s vowel production: Effects of language exposure and lexical frequency

Abstract: According to usage-based models of phonology, the more frequently a word is used and perceived in accented pronunciation variants, the more exemplars of accented tokens are stored and then used for subsequent productions of this word. This may lead to greater production variability in speakers with more variable input than in speakers with less variable input (cf. Pierrehumbert, 2001). This contrasts with abstractionist theories and with proposals according to which children unconsciously filter out accent fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 78 publications
1
9
0
Order By: Relevance
“…The fact that these never occur in monolinguals' English descriptions supports an analysis in terms of a structural innovation from French, boosting structural variability within English. Such bilingual increase in variation would be in line with what has been found in other linguistic domains, such as phonology (e.g., see Levy and Hanulíková, 2019…”
Section: Discussionsupporting
confidence: 86%
“…The fact that these never occur in monolinguals' English descriptions supports an analysis in terms of a structural innovation from French, boosting structural variability within English. Such bilingual increase in variation would be in line with what has been found in other linguistic domains, such as phonology (e.g., see Levy and Hanulíková, 2019…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, listeners with exposure to other varieties appear to be more tolerant to deviant exemplars, which leads the authors to conclude that phonological categories in these individuals might be less rigid than those for individuals without exposure. More recently, Levy and Hanulíková (2019) report that variability in vowel production on the part of children is related to their levels of non-native dialectal exposure.…”
Section: Individual Variability In the Tune-meaning Mappingmentioning
confidence: 99%
“…Relatedly, Babel et al (2019) suggest that social biases do not necessarily warp perception but exert their influences post-perceptually: They found that the pleasantness of the voice has little influence on listener adaptation to a new accent. Levy and Hanulíková (2019) show that vowel production by school-aged children was unaffected by whether they grow up bilingually or in a monolingual German home. Rather, variability in their own production was predicted by the variability across both foreign and regional accents to which they were exposed.…”
mentioning
confidence: 81%
“…Bradlow, Blasingame, and Lee (2018) conducted a sentence recognition experiment in order to determine how first and second language processing are affected by speaker intelligibility. Levy and Hanulíková (2019) asked how variable input due to word-frequency, dialect, and foreign accent affects school-aged children's vowel production.…”
mentioning
confidence: 99%
See 1 more Smart Citation